Navigating Healthcare's Digital Transformation : How Service Reliability and Digital Content Strategy Drive Patient Loyalty Through Trust - Ikhsan Febriansyah; Munawar Munawar; Endang Ruswanti (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
The digitalization of healthcare had prompted health institutions to adopt digital content marketing as an innovative strategy for service promotion and patient loyalty development, while preserving service reliability as a crucial loyalty factor. Recent empirical research had revealed inconsistent findings about the non-linear relationships among these variables, which necessitated additional investigation incorporating trust as a mediating factor. This research sought to provide empirical validation of how trust mediated the relationship between service reliability, digital content marketing, and patient loyalty within hospital settings. The study employed a cross-sectional methodology using purposive sampling with 119 outpatients from Hermina Kemayoran Hospital in Jakarta. The analytical approach utilized the three box method for descriptive analysis and Partial Least Square-Structural Equation Modeling (PLS-SEM) via Smart-PLS 4 for inferential analysis. Results demonstrated that both digital content marketing and service reliability influenced patient loyalty indirectly through trust mediation, though digital content marketing's indirect influence was considerably weaker than its direct impact. The research determined that trust served as a partial mediator in how digital content marketing and service reliability affected patient loyalty development in hospital environments.